The Representation of an Ideal Family in Neil Gaiman’s Coraline - Naraswari, Sastya; Wardani, L.D.P.; Basuki, Imam (PSGA Institut Agama Islam Tarbiyatut Tholabah, 2023)
The type of research used in this thesis is qualitative research in which the data are taken from collecting the words, quotations, sentence and narration that stated in Coraline by Neil Gaiman. The primary data are taken from Neil Gaiman’s Coraline in the form of dialogues, sentences, and narration stated by the character about how an ideal family is represented in the novel. Then, the secondary data are taken from books, internet, and another source related to the representation of an ideal family. This research analyzes the ideal family concept in Coraline by Neil Gaiman with the theory of representation by Stuart Hall. The concept of an ideal family is explained by using the constructionist approach and focuses on the discursive formation. The discursive formation is applied to analyze the discourse of an ideal family that is shown in Coraline. The finding of this research shows that the purpose of the main character, Coraline in hoping to have an ideal family in her life is to feel loved by her parents. The representation of an ideal family in Coraline is depicted through the two aspects, those are how they define a family, and the importance of a good parenting.